Pengaruh Pengetahuan Investasi, Return Investasi, Modal Minimal Investasi, dan Gaya Hidup Generasi Milenial Terhadap Minat Investasi - Lucky Ayu Damayanti; Nur Diana; Afifudin Afifudin (e_Jurnal Ilmiah Riset Akuntansi, 2023)
This research aims to determine how the influence of investment knowledge, investment return, minimum investment capital, and millennial generation's lifestyle on investment interest, either partially or simultaneously. The type of research used in this research is quantitative research with a causal associative approach. The population in this study is the millennial generation among active students of the Accounting Study Program, Faculty of Economics and Business, Islamic University of Malang and State University of Malang. The sampling technique in this research used purposive sampling with a total sample of 100 respondents. The method of data collection in this study used a questionnaire. To process all data or respondents' answers, the researcher used SPSS version 22 statistical tools by going through: validity test, reliability test, normality test, classical assumption test, multiple linear regression analysis, simultaneous test (F test), coefficient of determination (R²), and partial test (t test). Based on the results of the simultaneous test (F test) shows that investment knowledge, investment return, minimum investment capital, and millennial generation's lifestyle simultaneously have a significant effect on investment interest. Based on the results of the partial test (t test) shows that investment knowledge has no significant effect on investment interest, while investment returns, minimum investment capital, and millennial generation lifestyle have a significant positive effect on investment interest.Keywords: Investment knowledge, investment return, minimum investment capital, millennial generation lifestyle, investment interest.